Examining Callous‐unemotional Traits and Anxiety in a Sample of Incarcerated Adolescent Females. (12th April 2021) - Deskalo, Avital Y.; Fontaine, Nathalie M. G.
Abstract: Callous‐unemotional (CU) traits (e.g., lack of guilt and empathy) are a risk factor associated with antisocial behavior. Youth with CU traits can be differentiated by varying levels of co‐occurring anxiety. In this study, we examined CU variants in incarcerated adolescent females (n = 109) and their associations with emotional and behavioral problems and history of maltreatment. Semi‐structured interviews were also conducted with a subsample of the participants ( n = 13). Participants with CU traits and anxiety had similar levels of conduct problems compared to individuals with high CU traits without anxiety, but they reported more childhood maltreatment (especially sexual abuse).